History of Military Academies in Indonesia - Herlina, Nina (Diponegoro University, 2023)
The Military Academy in Indonesia has a rich history, established in different locations under various names until they were eventually merged. This study explores the dynamics of the Military Academies in Indonesia, from the Dutch East Indies era to the present day. It also investigates why Tidar Valley became the location for the Military Academy, considering both logical factors and local traditions? The research methodology employed in this study is the critical historical method, comprising four distinct stages heuristics, criticism, interpretation, and historiography. To explain why the Military Academy is located in the Tidar Valley, the author uses ideas from Robert von Heine Geldern and Gilbert J. Garraghan. This study reveals the dynamic development of the military academy in Indonesia. During the Dutch East Indies era, officer training took place at the Military Academy in Breda. Following World War II, a new Military Academy was established in Bandung in 1940. After Indonesia became independent in 1945, the Military Academy was established in Yogyakarta. Later on, more military education institutions appeared in various places like Tangerang, Mojoagung, Malang, Brastagi, Parapat, Bukittinggi, Palembang, Salatiga, and Bandung. In 1957, these institutions were combined to create the National Military Academy in Yogyakarta, which had branches for land, air, and sea. The land division became the Military Academy in 1965. In the same year, all division academies were merged into the Armed Forces Academy of the Republic of Indonesia (AKABRI), and the land division was renamed the Military Academy.